Motility Control of Symbionts and Organelles by the Eukaryotic Cell: The Handling of the Motile Capacity of Individual Parts Forges a Collective Biological Identity - Militello, Guglielmo (Frontiers in Psychology, 2019)
Motility occupies a decisive role in an organism’s ability to autonomously interact with its environment. However, collective biological organizations exhibit individual parts which have temporally or definitively lost their motor capacities, but still able to autonomously interact with their host. Indeed, although the flagella of bacterial symbionts of eukaryotic cells are usually inhibited or lost, they autonomously modify the environment provided by their host. Furthermore, the eukaryotic organelles of endosymbiotic origin (i.e. mitochondria and plastids) are no longer able to move autonomously; however, they make a cytoskeletal-driven motion that allow them to communicate with other eukaryotic cells and to perform a considerable number of physiological functions. The purpose of this paper is twofold: first, to investigate how changes in the motile capacities of the parts of a nested biological organization affect their interactive autonomy; second, to examine how the modification of the interactive autonomy of the individual part influences the constitutive autonomy of the collective association as a whole. The paper argues that the emergence and maintenance of collective biological identities involves a strict control of the motile abilities of their constituting members. This entails a reduction, but not necessarily a complete loss, of the agential capacities of the individual parts.